Does Seeing “Eye To Eye” Affect Work Engagement and Organizational Citizenship Behavior? A Role Theory Perspective on LMX Agreement - Matta, Fadel K.; Scott, Brent A.; Koopman, Joel; Conlon, Donald E. (Academy of Management Journal, 2015)
Despite meta-analytic evidence demonstrating that leader–member exchange (LMX) agreement (consensus between leader and subordinate perceptions) is only moderate at best, research on LMX typically examines this relationship from only one perspective: either the leader's or the subordinate's. We return to the roots of LMX and utilize role theory to argue that agreement between leader and subordinate perceptions of LMX quality has meaningful effects on employee motivation and behavior. In a polynomial regression analysis of 280 leader–subordinate dyads, employee work engagement—and subsequent organizational citizenship behavior (OCB)—was maximized (at each level of LMX quality) when leaders and subordinates were in agreement about the quality of their LMX relationship, but suffered when they did not see "eye to eye." Indeed, situations in which both leaders and subordinates evaluated their relationship as low quality were associated with higher work engagement (and subsequent OCB) than were situations of disagreement in which a single member evaluated the relationship as high quality. Further, this effect was consistent regardless of whether the leader or the subordinate evaluated the relationship highly. We conclude that, to fully understand the implications of our only dyadic leadership theory, we must consider the perspectives of both members of the LMX dyad simultaneously.